PEACEFUL JIHĀD DAN PENDIDIKAN DERADIKALISASI AGAMA - Sulasman, Sulasman (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
The Islamic Boarding School (Pondok Pesantren) Miftahul Huda was originatelly identical with the radicalism movement not only because of its exclusivism in religious activities, the criticism toward the government, but also the identification of its members with DI/TII movement and FPI. In line with internal and external dynamics, this boarding school reoriented its movement from physical jihād to the path of education and peaceful dakwah or in Lukens-Bull’s perspective it is so-called peaceful jihād. The process of self-domestication and the movement of de-radicalization in this boarding was executed by six ways. They are internalizing the values of boarding school, increasing the Islamic perspective, adopting schools system, providing the education of hubb al-waṭan, using local wisdom, and developing skill education. The strategy of de-radicalization applied by Miftahul Huda Islamic Boarding School is divided into three efforts; preventive de-radicalization, preservative de-radicalization, and curative de-radicalization. The results was shown that the students, alumni, and the boarding schools incorporated in Miftahul Huda Islamic boarding school networking system that appears in peace, moderate, and tolerance appearance.***Pondok Pesantren Miftahul Huda semula identik dengan gerakan “radikal” baik karena pandangan eksklusivismenya dalam beragama, kritisisme terhadap Pemerintah, maupun karena keidentikkan beberapa personalnya dengan gerakan DI/TII dan FPI. Sejalan dengan dinamika internal dan eksternal, pondok pesantren ini pun mereorientasi gerakannya dari jihād fisik ke jalur pendidikan dan dakwah damai atau dalam perspektif Lukens-Bull dikenal sebagai jihad damai (peaceful jihād). Proses menjinakkan diri dan gerakannya, yang dikenal dengan deradikalisasi, dilalui oleh pondok pesantren ini dengan enam cara, yakni internalisasi nilai-nilai pesantren, perluasan perspektif keislaman, adopsi sistem sekolah, pendidikan hubb al-waṭan, penggunaan local wisdom, dan pendidikan keterampilan. Upaya deradikalisasi yang dilakukan Pondok Pesantren Miftahul Huda berkisar pada tiga strategi, yakni pencegahan, pemeliharaan budaya damai, dan pemulihan bagi yang terdampak radikal. Hasilnya, para santri, alumni, dan pesantren yang tergabung dalam sistem jaringan Pondok Pesantren Miftahul Huda muncul dalam wajah damai, moderat, dan toleran.